A Socio-Technical Windows 11 Hardening Framework Integrating Ferret-Windows and CIS Benchmarks - Prasetyo Adi Wibowo Putro; Ray Novita Yasa Yasa; Mochammad Latief Reswandana Musonip; Dimas Nugroho Putro; Agry Zharfa (JURNAL TEKNIK INFORMATIKA, 2026)
The high level of vulnerability in the Windows operating system requires implementing a hardening strategy that focuses not only on technical security but also on end-user convenience. This study, using a Design Science Research (DSR) methodology, aims to design and evaluate a Windows-based host security configuration by applying 35 parameters developed by integrating the Ferret-Windows open-source tool and the Microsoft Windows 11 Benchmark CIS standard. The research method includes a descriptive study to analyze the effectiveness of the tool and its parameter formulation, and a prescriptive study to formulate a combined configuration. The evaluation was carried out through functional testing and usability measurements using the System Usability Scale (SUS) instrument for 31 end-users (e.g., staff and students) in a public institution context, using the System Usability Scale (SUS) instrument on a standardized test laptop. The results showed that the configured system obtained an average SUS score of 73.63, which falls within the "good" category according to the standard interpretation scale, indicating that the resulting system is usable by most users. These findings indicate that the proposed hardening framework results in a system configuration that achieves acceptable usability without significant user sacrifice. While the study’s limitations include a focus on usability rather than quantitative pre-/post-security validation, it provides a practical contribution, a socio-technical hardening framework adaptable for public institutions.